Caracterização morfoagronômica e molecular de feijão comum - Alves, Ludimila Pimenta (2016)
The common bean (Phaseolus vulgaris) is an important legume for the world population to be supplier of protein. The modernization of agriculture has caused the loss of genetic diversity bean. The activities of collection and characterization of germplasm possible to know regional genotypes and contribute to minimize the loss of genetic diversity. The aim of this study was to characterize 20 bean genotypes of germplasm bank of the Plant Production Department of School of Agricultural Sciences and Engineering at the Federal University of Espírito Santo, through morphological markers, living with spiderwort and molecular markers. They used commercial genotypes 5 and 15 regional acquired from family farmers in the Alegre county, Espírito Santo, Caparaó Capixaba region. Morphoagronomic analyzes were performed, analysis of coexistence with the weed Commelina diffusa and molecular analysis using 9 ISSR primers. The results showed that there was complete agreement between the groupings made by the qualitative and molecular characters. There is a significant genetic diversity in the sample bean genotypes from the Alegre county, Espirito Santo, Capixaba Caparaó region (regional), but between commercial genotypes, diversity is relatively narrow. Commercial cultivars showed little dissimilarity between themselves. The spiderwort can influence the development of the bean, and the cultivars may exhibit different behavior in relation to coexistence. The morphoagronomic and molecular characterization were effective in differentiating the genotypes and both accessions were considered distinct